Biodiversity Study of Black Coral (Order: Antipatharia) Collected from Manado, Indonesia based on rDNA Internal Transcribed Spacer (ITS) Sequences Analysis - HAPRY FRED NICO LAPIAN (Society for Indonesian Biodiversity, 2009)
Biodiversity of black coral (order Antipatharia) collected from the Bunaken Marine Park (Manado Sea, Indonesia) has been studied based on the sequence of the Internal Transcribed Spacers (ITS) region of rDNA gene. The results of the study showed that the 18 species of Antipatharia were considered to be separated in two family groups, family Myriopathidae and Antipathidae-Aphanipathida. A significant species-specific signal has been detected among the families of Antipathidae andAphanipathida. However, more studies-on different species were required to be clearly interpreted. The new species Pseudocirrhipathes mapia, the new genus Reticulopathes, and possibly a new taxon of the family Myriopathidae has beenrecognized based on ITS sequence data.Key words: biodiversity study, Manado, rDNA ITS, Antipatharia, black coral.